Analysis of the Influence of Workload, Wage Level, and Ritase on the Performance of Transport Service Drivers at PT Barokah Bumi Jaya - Wahid, Abdul; Fauzi, Akhmad (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to explain the impact of workload, wage amounts, and the number of trips on the performance of drivers, using the drivers of PT Barokah Bumi Jaya's transportation services as the research subject. This research employs a quantitative approach. The population of this study comprises drivers from PT Barokah Bumi Jaya's transportation services. The sample for this study consists of 32 drivers from PT Barokah Bumi Jaya's transportation services. All tests conducted using the SmartPLS application show that all the tests meet the prerequisites to be considered reliable. This study employs a quantitative research approach, and PLS and descriptive statistics are used in the data analysis. he study's findings show that driver performance is positively and significantly impacted by workload.